2002
DOI: 10.1063/1.1486481
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-nanotube-based resonant-circuit sensor for ammonia

Abstract: We present the design and development of highly sensitive and fast-responsive microwave resonant sensors for monitoring the presence of ammonia gas. The sensor consists of a circular disk electromagnetic resonant circuit coated with either single- or multiwalled carbon nanotubes that are highly sensitive to adsorbed gas molecules. Upon exposure to ammonia, the electrical resonant frequency of the sensor exhibits a dramatic downshift of 4.375 MHz. The recovery and response times of these sensors are nominally 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
163
0
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(174 citation statements)
references
References 7 publications
4
163
0
7
Order By: Relevance
“…With the rapid progress and improvement of nanotechnology, sensors fabricated by using carbon nanotubes (CNTs) as the sensing element were reported to give electrical response to different chemicals, such as NO 2 , NH 3 , CO, H 2 , and O 3 for gas detection [4][5][6][7][8][9]. CNT sensors provide high sensitivity, low power, and portable tools for in situ chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid progress and improvement of nanotechnology, sensors fabricated by using carbon nanotubes (CNTs) as the sensing element were reported to give electrical response to different chemicals, such as NO 2 , NH 3 , CO, H 2 , and O 3 for gas detection [4][5][6][7][8][9]. CNT sensors provide high sensitivity, low power, and portable tools for in situ chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of CNTs in practical applications was limited up to 2005 due to issues with fabrication and repeatability, lately they have been used in many domains, ranging from gas sensing and shielding to nanotube-based antennas and RF interconnects [2]- [13]. It has to be stressed that CNT mixtures/composites have been found to have electrical properties highly sensitive to extremely small quantities of gases, such as NH 3 , carbon dioxide (CO 2 ), nitrogen oxide (NO x ), etc., at room temperatures. CNTs have a very fast response time [2], which is a key feature for sensitive gas sensors.…”
Section: Date Of Publication: 5 May 2011mentioning
confidence: 99%
“…NH 3 is primarily a concern in areas of high agricultural activity because it is a natural waste product of livestock whereas it can also be a product of industrial sources, including the manufacturing of basic chemicals, metals, and textile products as well as automotive emissions. High levels of NH 3 can result in irritation to the eyes and respiratory tracts of humans and can negatively impact wildlife, livestock, and agricultural health. NO 2 is also a potentially toxic gas that can lead to respiratory symptoms in humans and detrimentally influence the growth of agriculture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent research has shown that the permittivity, ε r , and conductivity, σ, of a CNT is temporarily altered when it is subjected to certain gases, especially oxidizing/reducing gases such as NH 3 (ammonia) and O 2 (oxygen) [10]. This reaction has been exploited as a gas sensor by incorporating a thin layer of either randomly scattered SWNTs [11][12][13][14] or aligned multiwall nanotubes (MWNTs) [15] as part of a microwave resonator. The resonator center frequency shifts in direct response to the change in the permittivity of the CNT layer that occurs due to the presence of a reacting gas.…”
Section: Introductionmentioning
confidence: 99%